Current Problems of Entrepreneurship Regulation in the Republic of Kazakhstan - SHERIMOVA, Nurzat Sh.; TUKENOVA, Nataliya I.; BAIZHUMANOVA, Aigerim M.; MIRAMBAEVA, Gulnaz J.; AMIROVA, Bota K.; BEISENBIEV, Madi A. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
Transition to market economy requires far-reaching reforms of industrial structure focused on overcoming monopolism and strengthening competition. International practices confirm it’s impossible to solve this problem with no entrepreneurial development based on different forms of property.
Keywords: entrepreneurship; law; regulations; economy; development; policy; innovations; strategy; business